Analysis of Building Sanitation And Cleaning Facilities Case Study of Environmental Service Company - Purnomosutji Dyah Prinajati; Linda Noviana (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
This study aims to determine the sanitation conditions of buildings and cleaning facilities at an Environmental Services Company. In this research, the Importance Performance Analysis (IPA) mapping of each attribute of the assessment of the sanitation condition was evaluated so that it can be seen which assessment attributes have low values and need to be assessed to get corrective action as a top priority. This research is descriptive quantitative research by collecting data through direct observation and distributing questionnaires to all employees of the Environmental Services Company. The results of 20 respondents were processed using the SPSS 16 application. The results showed that the sanitation conditions of the buildings and cleaning facilities at the Environmental Service Company did not meet the requirements. Priority mapping of the sanitation attributes of buildings and cleaning facilities using the Importance Performance Analysis (IPA) method can be seen in the Cartesian diagram. The result shows that from all 17 building sanitation attributes, there are 3 attributes in quadrant A. While 7 attributes are in quadrant B, 3 attributes are in quadrant C, and 3 attributes are in quadrant D. Of the 46 sanitation attributes for sanitation facilities, there are 8 attributes in quadrant A, 24 attributes in quadrant B, 13 attributes in quadrant C, and 1 attribute in quadrant D. Attributes that have low scores on building sanitation, namely the yard and roof of the building, while in sanitation of cleaning facilities, namely lockers in the changing room, trash cans, and sanitary napkins.